'Managing Murdoch': How the regulator that became a problem then became a solution. (30th October 2012) - Purvis, Stewart
In 2009 David Cameron, the Leader of the British Conservative Party, then in opposition, announced that 'with a Conservative Government, Ofcom as we know it will cease to exist' (Tryhorn 2009; Holmwood 2009). He said the United Kingdom's communications regulator, the Office of Communications (Ofcom), would be cut back 'by a huge amount' and would 'no longer play a role in making policy'. Three years later, with Mr Cameron half-way through his term as Prime Minister of a Conservative-Liberal Democrat coalition government, Ofcom's budget had been cut – broadly in line with savings in the United Kingdom's other public bodies – but it had far from ceased to exist. In fact it had an even wider role in regulation. Cameron's government had asked Ofcom to regulate postal services in addition to its existing responsibilities for telecommunications and broadcasting.The British Prime Minister said the regulator's core functions were 'essential' (Leveson Inquiry 2012h: 50, par. 157). His government regularly asked for policy input from Ofcom and in 2011 sought advice on how to handle issues of media plurality (Department for Culture Media and Sport 2011). Understanding how such a sudden political change of heart came about provides a case study into an issue which goes far beyond the United Kingdom's shores – how political leaders, rather than submit to demands from news organizations for the de-regulation of their activities, may find that regulators are, in fact, a useful buttress against media pressure.